THE INFLUENCE OF PRICE, PROMOTION, AND PRODUCT QUALITY ON FASHION PRODUCT PURCHASE DECISIONS AT IRIAN SUPERMARKET TANJUNG MORAWA - Jonathan; Januardin; Br. Saragih , Rintan (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
Marketing is a very important strategy to introduce products and attract consumers, especially in the fashion sector which continues to develop following trends and lifestyles. Irian Supermarket located in Tanjung Morawa also provides fashion products, but is facing a decline in sales because it is unable to compete with specialty stores or online shopping platforms that offer more choices, more affordable prices, and products that are more in line with trend developments. Some of the reasons for the low consumer buying interest include relatively expensive prices, less attractive promotions, and product quality that has not met expectations. To increase the attractiveness of fashion products, this supermarket needs to review its pricing strategy, improve its promotional approach, and provide products with more modern quality and design. This study covers all visitors to Irian Supermarket Tanjung Morawa as the population, although the exact number is not clearly known or tends to be biased. Therefore, the sampling technique uses the Lemeshow formula, which is appropriate when the population size is not known for certain, so that one hundred people are determined as the research sample. The sampling method used is accidental sampling, which is the random selection of respondents based on who is willing and available when the research is conducted. The results of the study indicate that partially, price has a significant negative effect on purchasing decisions. Promotion has a significant effect on purchasing decisions partially. Product quality also shows a significant effect partially on purchasing decisions. Together, the variables price, promotion, and product quality have a significant effect on consumer purchasing decisions.